Doprowadź wyrażenie do najprostszej postaci
a) (3x-1)-(-x+3)=
b) (-8a+4)-(2a+7)=
c) (4x²-3x)+(x²-2x)=
d) (3x²-10)-(x²-6)=
e) (3b-4a²)-(-7b-3a²)=
f) (0,8x²+1,2y²)+(4,1x²-ax)=
g) (1,8ax-2,1ay)-(5,2ay-ax)=
h) (1 1/3a-3 2/5b)+(2 4/9a+1 1/15b)=
i) (0,5x+2 3/4y)-(1 3/5x-2,2y)=
j) (-6x²-2 1/7y)-(-0,7x²-4y)=

3

Odpowiedzi

2010-03-21T21:40:45+01:00
A) =3x-1+x-3=4x-4
b) = -8a+4-2a-7=-10a-3
c) =4x²-3x+x²-2x= 5x²-5x
d) =3x²-10-x²+6=2x²-4
e) =3b-4a²+7b+3a²=10b-a²
f) =0,8x²+1,2y²+4,1x²-ax=4,9x²+1,2y²-ax
g) =1,8ax-2,1ay-5,2ay+ax=2,8ax-7,3ay
2010-03-21T21:44:21+01:00
A)
(3x-1)-(-x+3)=
3x-1+x-3 =
4x-4

b)
(-8a+4)-(2a+7)=
-8a+4-2a-7 =
-10a-3

c)
(4x²-3x)+(x²-2x)=
4x²-3x+x²-2x =
5x²-5x

d)
(3x²-10)-(x²-6)=
3x²-10-x²+6 =
2x²-4

e)
(3b-4a²)-(-7b-3a²)=
3b-4a²+7b+3a² =
-a²+10b

f)
(0,8x²+1,2y²)+(4,1x²-ax)=
0,8x²+1,2y²+4,1x²-ax =
4,9x²+1,2y²-ax

g)
(1,8ax-2,1ay)-(5,2ay-ax)=
1,8ax-2,1ay-5,2ay+ax =
2,8ax-7,3ay

h)
(1 1/3a-3 2/5b)+(2 4/9a+1 1/15b)=
1⅓a-3⅖b+2⁴/₉a+1¹/₁₅b =
4a-2⅓b

i)
(0,5x+2 3/4y)-(1 3/5x-2,2y)=
0,5x+2,75y-1,6x+2,2y =
-1,1x+4,95y

j)
(-6x²-2 1/7y)-(-0,7x²-4y)=
-6x²-2¹/₇y+0,7x²+4y =
-5,3x²+1⁶/₇
2010-03-21T21:45:59+01:00
Doprowadź wyrażenie do najprostszej postaci
a) (3x-1)-(-x+3)=3x-1+x-3=4x-4
b) (-8a+4)-(2a+7)=-8a+4-2a-7=-10a-3
c) (4x²-3x)+(x²-2x)=4x²-3x+x²-2x=5x²-5x
d) (3x²-10)-(x²-6)=3x²-10-x²+6=2x²-4
e) (3b-4a²)-(-7b-3a²)=3b-4a²+7b+3a²=10b-a²
f) (0,8x²+1,2y²)+(4,1x²-ax)=0,8x²+1,2y²+4,1x²-ax=4,9x²+1,2y²-ax
g) (1,8ax-2,1ay)-(5,2ay-ax)=1,8ax-2,1ay-5,2ay+ax=2,8ax-7,3ay
h) (1 1/3a-3 2/5b)+(2 4/9a+1 1/15b)=1⅓a-3⅖b+2 4/9a+1 1/15b=1 3/9a+2 4/9a-3 6/15b+1 1/15b=3 7/9a-2 5/15b
i) (0,5x+2 3/4y)-(1 3/5x-2,2y)=0,5x+2¾y-1⅗x+2,2y=0,5x-1,6x+2,75y+2,2y=-1,1x+4,95y
j) (-6x²-2 1/7y)-(-0,7x²-4y)= -6x²-2 1/7y+0,7x²+4y=-5,3x²+1 6/7y